TRPC1/5-CaV3 Complex Mediates Leptin-Induced Excitability in Hypothalamic Neurons - Perissinotti, Paula P.; Martínez-Hernández, Elizabeth; Piedras-Rentería, Erika S. (Frontiers in Neuroscience, 2021)
Leptin regulates hypothalamic POMC+ (pro-opiomelanocortin) neurons by inducing TRPC (Transient Receptor Potential Cation) channel-mediate membrane depolarization. The role of TRPC channels in POMC neuron excitability is clearly established; however, it remains unknown whether their activity alone is sufficient to trigger excitability. Here we show that the right-shift voltage induced by the leptin-induced TRPC channel-mediated depolarization of the resting membrane potential brings T-type channels into the active window current range, resulting in an increase of the steady state T-type calcium current from 40 to 70% resulting in increased intrinsic excitability of POMC neurons. We assessed the role and timing of T-type channels on excitability and leptin-induced depolarization in vitro in cultured mouse POMC neurons. The involvement of TRPC channels in the leptin-induced excitability of POMC neurons was corroborated by using the TRPC channel inhibitor 2APB, which precluded the effect of leptin. We demonstrate T-type currents are indispensable for both processes, as treatment with NNC-55-0396 prevented the membrane depolarization and rheobase changes induced by leptin. Furthermore, co-immunoprecipitation experiments suggest that TRPC1/C5 channels and CaV3.1 and CaV3.2 channels co-exist in complex. The functional relevance of this complex was corroborated using intracellular Ca2+ chelators; intracellular BAPTA (but not EGTA) application was sufficient to preclude POMC neuron excitability. However, leptin-induced depolarization still occured in the presence of either BAPTA or EGTA suggesting that the calcium entry necessary to self-activate the TRPC1/5 complex is not blocked by the presence of BAPTA in hypothalamic neurons. Our study establishes T-type channels as integral part of the signaling cascade induced by leptin, modulating POMC neuron excitability. Leptin activation of TRPC channels existing in a macromolecular complex with T-type channels recruits the latter by locally induced membrane depolarization, further depolarizing POMC neurons, triggering action potentials and excitability.